One Rainy Day - Butler, M. Christina; Ill. Tina MacNaughton (New York Scholastic Inc., 2009)
Little Hedgehog is delighted when he wakes up to find it is raining. At last he can try out his lovely new raincoat, hat and boots, and his wonderful sparkly umbrella. But soon the rain gets faster and the wind gets blowier and Little Hedgehog's rainy day turns into a great big adventure.